Synthesis and analysis of nano-crystalline LiNiVO4 - Thongtem T. (2014)
LiNiVO4 was synthesized using Li2CO3, NH4VO3 and Ni(CH3COO)2.4H 2O as starting reagents and citric acid as a chelating agent. Mole ratios of metals to citric acid used for the preparation were 1:1-1:4. Carboxylate precursors were calcined at high temperatures to form powder. TGA data showed weight loss due to the evaporation and decomposition processes. FTIR showed the stretching bands of VO4 tetrahedron at 642, 713 and 813 cm-1. For 1 : 3 and 1 : 4 mole ratios, nano-crystals of inverse spinel LiNiVO4 (produced at 450°C calcination for 6 h) were detected by XRD, electron diffraction, SEM and TEM.